2022
DOI: 10.3390/jcm11102887
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Closed Incision Negative Pressure Therapy on the Medial Thigh Donor Site in Transverse Musculocutaneous Gracilis Flap Breast Reconstruction

Abstract: The objective of this study was to examine the impact of closed incision negative pressure therapy (CINPT) on donor site complications and patient perceptions in transverse musculocutaneous gracilis (TMG) flap breast reconstruction. Our institution conducted a retrospective cohort study, including all patients with TMG flap breast reconstruction from 1 January 2010 to 31 December 2021. Patients were grouped according to conventional wound management or CINPT. Outcomes were surgical site complications, fluid dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…21 Drains were left in place in the donor site in most of our included studies, but only four studies reported the average time these drains remained in their patients. 10,12,13,18 All four of these studies reported no significant difference in time to drain removal when comparing their ciNPT group and conventional dressings group. In the studies that reported drain output as a measure, there was no difference between the two groups as well.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…21 Drains were left in place in the donor site in most of our included studies, but only four studies reported the average time these drains remained in their patients. 10,12,13,18 All four of these studies reported no significant difference in time to drain removal when comparing their ciNPT group and conventional dressings group. In the studies that reported drain output as a measure, there was no difference between the two groups as well.…”
Section: Discussionmentioning
confidence: 97%
“…Selection bias is present in at least four of the included studies, as the authors acknowledge using ciNPT for wounds they deemed "high-risk," 14 or the authors switched their dressings after a certain time-point due to their clinical experiences. [16][17][18] Funnel plots were performed for each outcome analysis to test for publication bias. (See figure, Supplemental Digital Content 2, which displays funnel plots of standard error by log odds ratio assessing publication bias for the meta-analyses performed.…”
Section: Assessment Of Bias and Sensitivity Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Negative pressure wound therapy (NPWT), which is well known in the surgical field, is a platform that promotes wound healing by applying localized negative pressure to the wound 10 . Functionally, NPWT can remove excess fluid from the wound and provide a moist environment for wound healing 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Negative pressure wound therapy (NPWT), which is well known in the surgical field, is a platform that promotes wound healing by applying localized negative pressure to the wound. 10 Functionally, NPWT can remove excess fluid from the wound and provide a moist environment for wound healing. 11 In 1997, NPWT was introduced into clinical practice in its current form and used mainly in the treatment of chronic wounds, such as diabetic foot, and infected traumatic wounds.…”
Section: Introductionmentioning
confidence: 99%